1-Pyrroline-5-carboxylate released by prostate Cancer cell inhibit T cell proliferation and function by targeting SHP1/cytochrome c oxidoreductase/ROS Axis. Issue 1 (13th December 2018) - Yan, Yutao; Chang, Lei; Tian, Hongzhe; Wang, Lu; Zhang, Yawei; Yang, Tao; Li, Guohao; Hu, Weifeng; Shah, Kavita; Chen, Gang; Guo, Yonglian
Abstract : Background: Tumor cell mediated immune-suppression remains a question of interest in tumor biology. In this study, we focused on the metabolites that are released by prostate cancer cells (PCC), which could potentially attenuate T cell immunity. Methods: Prostate cancer cells (PCC) media (PCM) was used to treat T cells, and its impact on T cell signaling was evaluated. The molecular mechanism was further verified in vivo using mouse models. The clinical significance was determined using IHC in human clinical specimens. Liquid chromatography mass spectroscopy (LC/MS-MS) was used to identify the metabolites that are released by PCC, which trigger T cells inactivation. Results: PCM inhibits T cells proliferation and impairs their ability to produce inflammatory cytokines. PCM decreases ATP production and increases ROS production in T cells by inhibiting complex III of the electron transport chain. We further show that SHP1 as the key molecule that is upregulated in T cells in response to PCM, inhibition of which reverses the phenotype induced by PCM. Using metabolomics analysis, we identified 1-pyrroline-5-carboxylate (P5C) as a vital molecule that is released by PCC. P5C is responsible for suppressing T cells signaling by increasing ROS and SHP1, and decreasing cytokines and ATP production. We confirmed these findings in vivo, which revealed changed proline dehydrogenase (PRODH) expression in tumor tissues, which in turn influences tumor growth and T cell infiltration. Conclusions: Our study uncovered a key immunosuppressive axis, which is triggered by PRODH upregulation in PCa tissues, P5C secretion in media and subsequent SHP1-mediated impairment of T cell signaling and infiltration in PCa.